Parametres de reproduction des bovins zebu du Malawi - Kamwanja, L.A. (1992)
Describes part of a series of studies aimed at characterizing the pre-pubertal reproductive performance of the Malawi Zebu cattle, monitoring 10 Malawi Zebu heifers over a 15-month period starting when the animals attained 15 months of age and ending when they were 30 months old; and 10 multiparous Malawi Zebu X Brahman cows were monitored for estrus immediately post partum until they were bred; w. partic. ref. to uterine involution, calving to first estrus, calving to first ovulation, calving to conception, calving interval, first estrus-conception, and to days to first rise in progesterone.